The use of a neighborhood park by visitors with different cultural backgrounds - Mantere, Johanna (2008)
As pleasant and healthy environments, parks should be open, multicultural places, with an easy access for all. It is not only the location of a park, but also its qualities that allow it to be used for desired purposes that make it accessible for people. The aim of this study is therefore to identify variations in the ways of the use of a park called Gubbaparken, (situated in Helsingborg, Sweden,) between different social groups, with specific focus on ethnicity. According to the result of the study, the visitors carry out activities of different social and beneficial or profitable importance to them. Which activities are preferred most often, depends on whether the cultural values the visitors represent are predominantly collectivistic, individualistic, urban, rural, abstract, concrete, or what the persons age, level of acculturation, family situation or social status (such as advantaged or disadvantaged) is. According to the visitors of "Gubbaparken", it should provide possibilities for group gatherings, play and sports, social contact with new people, but also solitude and calmness and more stimulating visual experiences. How these values form the visitors' ideals of an attractive park, and how the possibilities to activities correspond to these ideals, should be contemplated carefully when planning urban parks and green spaces.